COVID‐19 in solid organ transplant recipients: Initial report from the US epicenter. Issue 7 (10th May 2020) - Pereira, Marcus R.; Mohan, Sumit; Cohen, David J.; Husain, Syed A.; Dube, Geoffrey K.; Ratner, Lloyd E.; Arcasoy, Selim; Aversa, Meghan M.; Benvenuto, Luke J.; Dadhania, Darshana M.; Kapur, Sandip; Dove, Lorna M.; et al.
Abstract : Solid organ transplant recipients may be at a high risk for SARS‐CoV‐2 infection and poor associated outcomes. We herein report our initial experience with solid organ transplant recipients with SARS‐CoV‐2 infection at two centers during the first 3 weeks of the outbreak in New York City. Baseline characteristics, clinical presentation, antiviral and immunosuppressive management were compared between patients with mild/moderate and severe disease (defined as ICU admission, intubation or death). Ninety patients were analyzed with a median age of 57 years. Forty‐six were kidney recipients, 17 lung, 13 liver, 9 heart, and 5 dual‐organ transplants. The most common presenting symptoms were fever (70%), cough (59%), and dyspnea (43%). Twenty‐two (24%) had mild, 41 (46%) moderate, and 27 (30%) severe disease. Among the 68 hospitalized patients, 12% required non‐rebreather and 35% required intubation. 91% received hydroxychloroquine, 66% azithromycin, 3% remdesivir, 21% tocilizumab, and 24% bolus steroids. Sixteen patients died (18% overall, 24% of hospitalized, 52% of ICU) and 37 (54%) were discharged. In this initial cohort, transplant recipients with COVID‐19 appear to have more severe outcomes, although testing limitations likely led to undercounting of mild/asymptomatic cases. As this outbreak unfolds, COVID‐19 has the potential to severely impact solid organ transplant recipients. Abstract : In this multicenter study of 90 solid organ transplant recipients diagnosed with COVID‐19 during the first three weeks of the outbreak in New York City, the authors report on the clinical presentation, laboratory abnormalities, risk factors, disease severity, and outcomes.